Applied Potential Dependent Growth of Sno 2 Nanostructures by Anodic Oxidation of Tin - Singh, D (2012)
Nanothread, nanotetrapod and nanocube like structures of SnO 2 have been synthesized by anodic oxidation through a simple electrolysis process utilizing tin as a sacrificial electrode. The synthesized nanostructures were dependent to applied potential between the electrodes. The method is based on anodization pursuant to the simple electrolysis of plain water (with ionic conductivity 6-10 ?S/m and pH ~ 6.5) at different voltages. The platinum and tin were utilized as cathode and anode respectively. The applied potential was varied 2 V, 4 V, 6 V and 8 V to see it s effect on the growth of nanostructures. The synthesized materials were delaminated in the electrolyte. TEM characterization of the material as synthesized and settled down at the bottom of the electrolytic cell after electrolysis revealed the nanothread like structures at 2 V, nanotetrapod like structures at 4 and 6 V and nanocube like structures at 8 V. A tentative explanation for the formation and growth of SnO 2nanostructures has also been given. © 2012 American Scientific Publishers. All rights reserved.
Keywords: Anodic oxidation; Nanocubes; Nanotetrapods; Nanothreads; SnO2 nanostructures